PENGARUH ENVIRONMENT, SOCIAL, GOVERNANCE (ESG) DISCLOSURE TERHADAP MARKET VALUE DENGAN ENVIRONMENTAL RISK OF INDUSTRY SECTOR SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan yang terdaftar pada Indeks JII70 (Jakarta Islamic Index 70) BEI periode 2019-2022) - Audito, Judhistira; Yuyetta, Etna Nur Afri (Diponegoro Journal of Accounting, 2024)
This study aims to examine the effect of ESG Disclosure on Market Value and to examine Environmental Risk of Industry Sector as a moderating influence between ESG Disclosure and Market Value. The independent variable of this study, ESG Disclosure is measured using the ESG Disclosure Score published by Bloomberg Terminal, for the dependent variable Market Value is measured using Tobin's Q ratio, and for the moderating variable Environmental Risk of Industry Sector is measured using GHG Emission, Climate change risk, and Energy Consumption Disclosure with content analysis. This study uses leverage and firm size as control variables. The population in this study are companies listed on the JII70 Index (Jakarta Islamic Index 70) consecutively during the 2019-2022 period. Sampling was carried out using purposive sampling method which is sampling based on certain predetermined criteria. The total number of companies sampled was 110 companies, the analysis method in this study was the MRA (Moderated Regression Analysis) method. The results of the study show that ESG Disclosure has a significant positive effect on Market Value, and Environmental Risk of Industry Sector weakens the relationship between ESG Disclosure and Market Value.